Psychoeducational intervention in students with autism spectrum disorders’ relatives - Adianelys Oduardo Pérez; Enmanuel de Jesús LLanes Oduardo; Angel Luis Gómez Cardoso; Rolando Rodríguez Puga (Medisur)
Background: “autism spectrum disorder” is an entity of neurobiological origin, characterized by a variety of signs and symptoms. Objective: raise the knowledge level in relatives of students with autism spectrum disorder. Methods: a quasi-experimental study of educational intervention was carried out in the nine Rehabilitation Services of the Camagüey municipality health areas, from January to December 2022. The sample consisted of 25 family members who met the eligibility criteria. To evaluate the results of the intervention, a questionnaire was applied before and after the intervention was developed. Results: there was a predominance of the female sex 23 (92%), an age range of 30-39 years 11 (44%) and a high school level 13 (52%). Before the intervention, the level of general knowledge about autism spectrum disorder was insufficient by 68%. Regarding emotional competence, it reached 84%, the indicated treatment 84%, and educational methods 60%. After the strategy, it was possible to raise the level of general knowledge by 100%, 92% achieved the objective of emotional competence, 100% achieved sufficiency regarding the indicated treatment and 92% obtained improvement in educational styles knowledge. Conclusions: it was possible to raise the level of general knowledge about autism spectrum disorder, emotional competence, compliance with neurosensory treatment and educational styles.